COMPREHENSIVE ASSESSMENT OF THE MARKET DRUGS FOR TREATMENT OF PNEUMONIA IN PEDIATRICS - D. D. Siukaeva; O. D. Nemyatyh; I. A. Narkevich; N. I. Pavlenko (Разработка и регистрация лекарственных средств)
The results of present work show that the largest (52%) share of drugs for etiotropic therapy of pneumonia in pediatrics is represented by foreign manufacturers. Asian countries (India (38,45%) and China (6,46%) bring the most contribution into the structure of import. Drugs in form of powders and lyophilizates (43,20%), tablets (36,66%), and injections (11,72%) have the largest specific weight on market. The fraction of substances (83,75%) in the structure of import supply indicates the dependence of local manufacturers on raw material from abroad. The presentation of beta-lactam antibiotics (drugs - 45,70%, pharmaceutical substances - 36,98%) is most frequent. It's important to notice that only 50% of drugs for pneumonia therapy may be allowed to use for children under 3 years. The monitoring of side effects in pediatrics results (meronem, cephtriaxon, ciprofloxacin and cephtazidim) shows high probability of developing of adverse effects from digestive and nervous systems.